Pengaruh Model Pembelajaran STAD (Student Team Achievement Divisions) terhadap Kemampuan Manganalisis Struktur Teks Eksplanasi Siswa Kelas XI SMA Negeri 2 Lubuklinggau - Febriani, Wuri Intan; Effendi, M. Syahrun (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study was to determine the effect of the STAD (Student Team Achievement Divisions) learning model on the ability to analyze the explanatory text structure of class XI students of SMA Negeri 2 Lubuklinggau. The research method used a pure experimental method with a pre-test-post-test control group research design. The population of this study was 198 high school class XI students consisting of 6 classes. The sampling technique used Cluster Random Sampling technique and the research sample was class XI IPA 1 totaling 33 as the experimental class and class XI IPA 3 with 35 as the control class. Data collection using test techniques and analyzed using the "t" test formula. Based on the results of data analysis, then t hit was consulted with t tab with a significance level of 5%. Because dk = 68 is not in the table, the t tab value with dk = 70 at the 5% confidence level is 2.00. Thus, t hit: 2.93> t tab: 2.00. Thus, the STAD learning model can have an influence on the ability to analyze the structure of the explanatory text of class XI students of SMA Negeri 2 Lubuklinggau.